Multi-Scale Comparison of Physicochemical Properties, Refined Structures, and Gel Characteristics of a Novel Native Wild Pea Starch with Commercial Pea and Mung Bean Starch - Xiaojun Zhang; Ning Tang; Xin Jia; Donghui Geng; Yongqiang Cheng (Foods, 2023)
In the present study, the morphology, refined structure, thermal properties, and dynamic rheological, texture, and digestive properties of common vetch starch, a potential new type of legume starch, were systematically investigated, and compared with commercially available pea and mung bean starch. The results showed that the composition and chemical structure of common vetch starch were similar to the pea and mung bean starch. However, the amylose content (35.69), A-chain proportion (37.62), and relative crystallinity (34.16) of common vetch starch were higher, and the particle size and molecular weight (44,042 kDa) were larger. The value of pasting properties and enthalpy change (ΔH) of gelatinization of common vetch starch was lower and higher than mung bean and pea starch, respectively, and a lower swelling power and pasting index indicate that common vetch starch had higher hot-paste and cold-paste stability. In addition, common vetch starch gel exhibited good rheology, cohesiveness, and anti-digestive properties. These results provide new insights into the broader application of common vetch starch.